Fatal drug use in the COVID-19 pandemic response: Changing trends in drug-involved deaths before and after stay-at-home orders in Louisiana - Leonhardt, Maxwell M.; Spartz, John R.; Shankar, Arti; Murphy, Stephen A. (Frontiers in Public Health, 2023)
The effect of disaster events on increasing drug-involved deaths has been clearly shown in previous literature. As the COVID-19 pandemic led to stay-at-home orders throughout the United States, there was a simultaneous spike in drug-involved deaths around the country. The landscape of a preexisting epidemic of drug-involved deaths in the United States is one which is not geographically homogenous. Given this, state specific analysis of changing trends in drug-use and drug-involved deaths is vital to inform both care for people who use drugs and local policy. An analysis of public health surveillance data from the state of Louisiana both before and after the initial stay-at-home order of the COVID-19 pandemic was used to determine the effect the pandemic may have had on the drug-involved deaths within this state. Using linear regression analysis of total drug-involved deaths, as well as drug specific subgroups, trends were measured based on quarterly (Qly) deaths. With the initial stay-at-home order as the change point, trends measured through quarter 1 (Q1) of 2020 were compared to trends from quarter 2 (Q2) 2020 through quarter 3 (Q3) of 2021. The significant increased rate of change in Qly drug-involved deaths, synthetic opioid-involved deaths, stimulant-involved deaths, and psychostimulant-involved deaths indicate a long-term change following the initial response to the COVID-19 pandemic. Changes in the delivery of mental health services, harm reduction services, medication for opioid use disorder (MOUD), treatment services, withdrawal management services, addiction counseling, shelters, housing, and food supplies further limited drug-involved prevention support, all of which were exacerbated by the new stress of living in a pandemic and economic uncertainty.